ANALISIS PUISI SAPARDI DJOKO DAMONO “CERMIN 1” DENGAN PENDEKATAN SEMIOTIKA - Imas City; Neng Shalihah; Restu Bias Primandika (IKIP Siliwangi, 2018)
This study aims at (1) analysing the poem entitled Cermin 1semiotically (2) describing the results of the analysis of poem entitled Mirror 1 by Sapardi Djoko Damono and (3) defining the outline of the theme of the poem. Descriptive method is used to describe the contents of a poem. The poem Cermin 1 was analysed semiotically to acknowledge the meaning and signs of literary words so that the meaning could be conveyed to readers. The result shows that the poem has a function to declare something that is not textual, but the mirror only wants to show it, not voicing. Therefore, the shadow on the mirror can introspect itself because the shadow couldnever did such bad deeds. It can only be silenced in the mirror as a signified, with a mirror its signifier.